ADMINISTRATION OF REWARD FOR INDIVIDUAL PERFORMANCE AS A PREDICTOR OF ORGANIZATIONAL COMMITMENT - Azman Ismail; Anis Anisah Abdullah (Economic Review)
This study was done to assess the correlation between administration of reward for individual performance and organizational commitment. A quantitative survey method was employed to collect data from employees at fire and rescue organizations in Malaysia. The results of SmartPLS path model analysis revealed that administration of reward for individual performance was positively and significantly correlated with organizational commitment. In sum, this result demonstrates that the competency of administrators to appropriately implement communication, participation and performance appraisal in managing reward for individual performance may lead to an enhanced organizational commitment in the organizational sample. The paper provides discussion, implications and conclusion.